Tanggung Jawab PT. Guntur Kharisma Perkasa Terhadap Pemutusan Hubungan Kerja; Studi Putusan Mahkamah Agung Nomor: 641K/Pdt.Sus-PHI/2018 - Raines Indah Mutiara; Muhammad Ali Hanafiah Selian (JOURNAL of LEGAL RESEARCH, 2019)
Abstract:Termination of Employment is the termination of employment due to a certain reason that results in the termination of rights and obligations between workers or laborers and employers. This can happen to business entities that are incorporated or not incorporated. Including happens to entities owned by individuals, belonging to associations, or other legal entities, both private and state owned. This includes social enterprises and other businesses that have management and employ others by paying wages or other forms of compensation. This study aims to find out the form of corporate responsibility after terminating employment, and the suitability of the arguments in the Supreme Court Decision Number 641 K / Pdt.Sus-PHI / 2018. This study uses a type of normative juridical research and library research by conducting an assessment of applicable laws and regulations that support the results of a study. The results showed that the Supreme Court Decision Number 641 K / Pdt.Sus-PHI / 2018 is not much different and gives legal power over the First Level Decision Number 37 / Pdt.Sus-PHI / 2017 / PN Smr. In Decision Number 641 K / Pdt.Sus-PHI / 2018 the Panel of Judges in its consideration was fair enough in providing legal protection for workers who were terminated, in order to fulfill compensation for workers' rights that should have been accepted in accordance with Law Number 13 2003 About Employment.Keywords: Termination of Employment, Workers, Companies, Employment Relations